2019
DOI: 10.3389/fphar.2019.01484
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Research Reproducibility: Keeping Up High Standards

Abstract: Concern regarding the reproducibility of observations in life science research has emerged in recent years, particularly in view of unfavorable experiences with preclinical in vivo research. The use of cell-based systems has increasingly replaced in vivo research and the application of in vitro models enjoys an ever-growing popularity. To avoid repeating past mistakes, high standards of reproducibility and reliability must be established and maintained in the field of in vitro biomedical research. Detailed gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 90 publications
(85 reference statements)
0
75
0
4
Order By: Relevance
“…neuroscience, immunology, developmental science) in preclinical science. In particular, the inclusion of non-animal (cell) research in the present work is distinctive since reporting is often not presented as a component of reproducibility in research conducted in vitro 24 . Future investigation on the quality of reporting in research made in vitro might be useful.…”
Section: Discussionmentioning
confidence: 99%
“…neuroscience, immunology, developmental science) in preclinical science. In particular, the inclusion of non-animal (cell) research in the present work is distinctive since reporting is often not presented as a component of reproducibility in research conducted in vitro 24 . Future investigation on the quality of reporting in research made in vitro might be useful.…”
Section: Discussionmentioning
confidence: 99%
“…3D culture systems provide a tremendous opportunity to explore cancer immunology, but they are not without limitations. The increased complexity of 3D systems can make inter- and intra-experiment reproducibility difficult [ 113 ]. 3D culture systems are more expensive and less widely available than 2D culture systems.…”
Section: Limitationsmentioning
confidence: 99%
“…Reviewing the literature shows that reproducibility in the data and analysis is the subject of an extensive range of publications in different areas of science, e.g., life science, bioscience, medical and pharmaceutical science and translational science [2][3][4][5][6]. Studies have shown irreproducibility of results is often due to poor documentation of the statistical method [7][8][9]. This is especially critical for the high-throughput phenomic screening when tens of thousands of data points are generated and analysed.…”
Section: Introductionmentioning
confidence: 99%